2005
DOI: 10.1117/1.2141624
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of meningioma by time-resolved fluorescence spectroscopy

Abstract: We investigate the use of time-resolved laser-induced fluorescence spectroscopy (TR-LIFS) as an adjunctive tool for the intraoperative rapid evaluation of tumor specimens and delineation of tumor from surrounding normal tissue. Tissue autofluorescence is induced with a pulsed nitrogen laser (337 nm, 1.2 ns) and the intensity decay profiles are recorded in the 370 to 500 nm spectral range with a fast digitizer (0.2 ns resolution). Experiments are conducted on excised specimens (meningioma, dura mater, cerebral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 30 publications
(50 reference statements)
1
58
0
Order By: Relevance
“…Tumor metabolic stages and the amount of molecules present in tissue may be the responsible of changes in the decays. Butte et al (2005) described the potential use of time-resolved fluorescence spectroscopy as an adjunctive tool for the intraoperative rapid evaluation of meningioma diagnosis. They evaluated the technique on ex vivo tissue specimens from patients undergoing brain tumor surgery and the results showed a sensitivity higher than 89%, specificity of 100% and an accuracy of classification around 92% [13].…”
Section: Discussionmentioning
confidence: 99%
“…Tumor metabolic stages and the amount of molecules present in tissue may be the responsible of changes in the decays. Butte et al (2005) described the potential use of time-resolved fluorescence spectroscopy as an adjunctive tool for the intraoperative rapid evaluation of meningioma diagnosis. They evaluated the technique on ex vivo tissue specimens from patients undergoing brain tumor surgery and the results showed a sensitivity higher than 89%, specificity of 100% and an accuracy of classification around 92% [13].…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the fluorescence properties of these molecules can report on altered metabolism, protein cross links, cell signalling and even disease state [15,[17][18][19]. In particular the fluorescence lifetime of endogenous fluorophores, which is relatively insensitive to fluorophore concentration and to signal attenuation by the sample, has been shown (both ex vivo and in vivo) to effectively differentiate between healthy and diseased tissue, for example in atherosclerotic plaques [20,21] and in various types of cancer [22][23][24][25][26][27][28][29][30][31]. Accordingly, there is significant interest in the development of instruments that can measure the autofluorescence properties of skin for clinical diagnosis, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of lipid partitioning and fatty acid oxidation can be modeled by monitoring electron transfer flavoprotein autofluorescence (Lam et al, 2012). Finally, quantitative studies using cellular autofluorescence have revealed distinct differences between healthy and cancer cells (Butte et al, 2005;Mayevsky and Barbiro-Michaely, 2013;Pavlova et al, 2008). As multiphoton excitation microscopy, fluorescence lifetime imaging and timeresolved fluorescence anisotropy techniques become readily available from commercial sources, applying measurements of autofluorescence to intraocular imaging will enable in vivo longitudinal studies in a variety of biological systems.…”
Section: Discussionmentioning
confidence: 99%